Accessibility Strategies in a Mobile Card Game - de Castro, Rute Nogueira Silveira; Andrade, Rossana Maria de Castro; Darin, Ticianne de Gois Ribeiro; Carvalho, Leandro A.; Carneiro, Nayana; Araújo, Maria (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
Mobile games represent an important branch of the entertainment industry, and have increased their potential during the pandemic. However, some aspects of mobile games are often denied to people with special needs, similarly to what happens with traditional games available in the market, in which accessibility features are usually minimal. In order to fill this gap, research groups, stakeholder communities and software companies continuously develop games directly designed for users with specific disabilities. Nevertheless, there are a generous amount of games already developed that need to adapt to accessibility needs. Therefore, there is a need for development teams to use techniques to make this adaptation possible, leading them to the implementation of consistent accessibility features that contemplate several accessibility needs beyond what the device itself brings. Thus, this work presents the experience of increase the software quality, by improvement of acccessibility as a usability subcharacteristic of a software product model, in a traditional mobile card game case by applying strategies to promote a better user experience for people with impaired vision. In addition, an accessibility evaluation of this mobile card game was done to verify whether we can confirm that the strategies adopted in the game development mechanics improved the user experience.